60=6*6-2n

Simple and best practice solution for 60=6*6-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=6*6-2n equation:


Simplifying
60 = 6 * 6 + -2n

Multiply 6 * 6
60 = 36 + -2n

Solving
60 = 36 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
60 + 2n = 36 + -2n + 2n

Combine like terms: -2n + 2n = 0
60 + 2n = 36 + 0
60 + 2n = 36

Add '-60' to each side of the equation.
60 + -60 + 2n = 36 + -60

Combine like terms: 60 + -60 = 0
0 + 2n = 36 + -60
2n = 36 + -60

Combine like terms: 36 + -60 = -24
2n = -24

Divide each side by '2'.
n = -12

Simplifying
n = -12

See similar equations:

| 8x+5.94=2x+12 | | (2n+2)(6n+1)=9 | | 3m-7m+13=21 | | (3*4)-(1+2)=11 | | 2(1)+3=5 | | 8z+1=4 | | 10y-82=-y+72 | | 7+77x=33x+15 | | 5-7n+4n=33-73 | | 3(8x+4)x=6 | | 20y+5=10 | | 2f+3=f+6 | | 47-14=14 | | Q+2.7= | | t+4x-9=-6 | | 99x+78y=198 | | 41-2x=-37-9x | | -12x+(-8x)=140 | | (2x-27)=95 | | 2x-5+b=180 | | 14xy+3y=24 | | 2x-5+b=170 | | 4d-8=16 | | n+x-20=0 | | 22d^4-94d^3+24d^2= | | 210=61m | | x-5-18= | | 6y-78=126-11y | | lne^5x-2/x | | 8x-39/-13=11 | | -2(2x+7)-7(-8x-6)=76 | | log[1/4](3^3) |

Equations solver categories